Inclusive Plurilingual Classrooms. Teacher Awareness, Climate, and Social and Emotional Learning: Recommendations for Practice in CLIL and Beyond - Mortimore, Louisa (IGI Global, 2024)
The shift of plurilingual and bilingual streams into mainstream education has highlighted the need for inclusive teaching practices to support learning in diverse contexts. While research evidences the need for improved methodological training, there is less focus on providing teachers with the training needed in a diverse classroom with pupils who require educational support, despite increasing numbers in schools. Teachers need to be aware that providing a constructive classroom climate is crucial in creating an inclusive classroom. Similarly, developing the social and emotional competences of pupils promotes prosocial skills such as supportive peer relationships and empathy, necessary traits in the diverse classroom. This chapter presents a theoretical perspective on the emotional, social, and psychological benefits of providing a supportive and inclusive classroom climate in plurilingual and bilingual education and discusses how pedagogical and metacognitive strategies, as promoted in CLIL, can be used as everyday strategies to scaffold learning in the inclusive classroom.
Keywords: inclusive plurilingual classrooms; social and emotional learning; CLIL